Mechanobiology of Autophagy: The Unexplored Side of Cancer - Hernández-Cáceres, Maria Paz; Munoz, Leslie; Pradenas, Javiera M.; Pena, Francisco; Lagos, Pablo; Aceiton, Pablo; Owen, Gareth I.; Morselli, Eugenia; Criollo, Alfredo; Ravasio, Andrea; Bertocchi, Cristina (Frontiers in Oncology, 2021)
Proper execution of cellular function, maintenance of cellular homeostasis and cell survival depend on functional integration of cellular processes and correct orchestration of cellular responses to stresses. Cancer transformation is a common negative consequence of mismanagement of coordinated response by the cell. In this scenario, by maintaining the balance among synthesis, degradation, and recycling of cytosolic components including proteins, lipids, and organelles the process of autophagy plays a central role. Several environmental stresses activate autophagy, among those hypoxia, DNA damage, inflammation, and metabolic challenges such as starvation. In addition to these chemical challenges, there is a requirement for cells to cope with mechanical stresses stemming from their microenvironment. Cells accomplish this task by activating an intrinsic mechanical response mediated by cytoskeleton active processes and through mechanosensitive protein complexes which interface the cells with their mechano-environment. Despite autophagy and cell mechanics being known to play crucial transforming roles during oncogenesis and malignant progression their interplay is largely overlooked. In this review, we highlight the role of physical forces in autophagy regulation and their potential implications in both physiological as well as pathological conditions. By taking a mechanical perspective, we wish to stimulate novel questions to further the investigation of the mechanical requirements of autophagy and appreciate the extent to which mechanical signals affect this process.